1993
DOI: 10.1002/jbm.820270508
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate particles enhance DNA and protein synthesis of human fibroblasts in vitro

Abstract: Aseptic loosening of polymethylmethacrylate (PMMA) fixed prosthesis is characterized by formation of a radiolucent fibrous membrane, accumulation of inflammatory cells and osteolysis. Since this membrane is produced by fibroblasts, it is likely that these connective tissue cells play a critical role in the loosening process. Whether fibroblasts form the radiolucent membrane in response to stimulation by PMMA has not yet been established, nor is it known whether fibroblasts play a role in attracting inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Two previous studies have shown a humeral interaction between macrophages and fibroblasts. 9,15 Conditioned medium from macrophages exposed to phagocytosable particles induced a proliferative response in fibroblasts. Macrophage-fibroblast interactions involving cytokine release have been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have shown a humeral interaction between macrophages and fibroblasts. 9,15 Conditioned medium from macrophages exposed to phagocytosable particles induced a proliferative response in fibroblasts. Macrophage-fibroblast interactions involving cytokine release have been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially prepared polybead PMMA and PS microspheres measuring .325 micrometers in diameter were obtained from Polysciences (Warrington, Pennsylvania) and were sterilized by exposure to UV irradiation overnight, as previously described. 20 These particles were screened for endotoxin using a Sigma Biosciences endotoxin kit assay. There was no detectable endotoxin in the particles used in this study.…”
Section: Particle Preparationmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] These studies, which have documented the direct effect of particle wear debris, such as titanium alloy, polyethylene, and polymethylmethacrylate particles, on monocyte/macrophage function, used either commercially prepared particles or particulate wear debris retrieved from revision surgery. Exposure of monocytes/macrophages and synoviocytes to these particles resulted in the release of inflammatory cytokines, [10][11][12][13][14][15][16][17][18][19][20][21][22] demonstrating that wear particles may directly activate mononuclear inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…65 Frondoza et al, Maloney et al, and Manlapaz et al reported that fibroblasts respond to PMMA particles and metallic particles through increased cell proliferation and release of proinflammatory cytokines and degradative enzymes. 29,66,67 Fibroblasts also respond to particulate debris through the release of prostaglandin E2, IL-6, and up-regulation of collagenase activity. 29,33 Different distributions of cell types in membranes harvested from different patients undergoing revision arthroplasty suggest that the response to orthopedic wear debris may be patient specific.…”
mentioning
confidence: 99%